Window Gazes and World Views: A chapter in the Cultural History of Vision - Jütte, Daniel (Critical inquiry, 2016)
Until only a few decades ago, one of the most popular leisure activities in Europe was simply looking out the window. Consider Germany, where leisure has been the subject of sociological study for more than half a century: in the 1950s, gazing from windows ranked sixth in a list of favorite national leisure activities, surpassed only by reading, gardening, shopping, fixing up one's home, and playing with one's children. As those who grew up during that time recall, people would stand at their windows for hours and look out. Here, Jutte examines a chapter in the cultural history of vision.